(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The oppressive patriarchal biopolitical relationships, transfigured in biopower practices have underestimated and / or made women’s work invisible, making this process more intense in rural areas. Considering the theme presented above, through a hypothetical-deductive study, with bibliographic review, it is intended to reflect how the biopower practices existing in patriarchal society intensify the stereotyping and naturalization of female oppression and, how this has affected the peasants, to then verify how social movements have contributed to the identity recognition and income redistribution of peasants in Brazil. Thus, the strong power of patriarchal culture was contacted in an attempt to establish female identities and, from them, inhabit the female zoé, which occurs more intensely in rural areas. Through social movements, peasant women have legally gained recognition for their work, giving rise to citizenship rights. However, the change must also happen in the cultural sphere, leaving the zoé condition for the past.